THE EFFECTIVENESS OF ONLINE INSTRUCTIONAL VIDEOS IN TEACHING STUDENT SPEAKING SKILL - Zaitun Zaitun; Muhamad Sofian Hadi; Aryani Syalwa Putri (Eltin Journal : Journal of English Language Teaching in Indonesia, 2021)
This study aims to find out whether there is significant effect of teaching speaking using online instructional videos to the students’ speaking achievement. This reserch used quantitative research method. Pre-experimental design was employed in this research. Ten grade students of An-Nuqthah of Islamic Senior High School were chosen as the sample of this research. The sample was selected by using random sampliong technique. The instruments of this research are pre-test and post-test. Then, the data obtained were analyzed statistically. The statistical analysis results showed that the mean score of the students in the pretest was 41.07 and the mean score of posttest was 82.14. In addition, the value of tcal (4.49) was higher than ttable (1.782). It means that the use of online instructional video was considered effective in improving students’ speaking skill. From this research, the teachers are recommended to use online instructional video as the median in teaching speaking.